2017
DOI: 10.25299/jshmic.2017.vol4(2).536
|View full text |Cite
|
Sign up to set email alerts
|

Developing Cooperative Learning Based E-Module to Teach Basic English Grammar of the First Semester of English Study Program Students at FKIP – UIR

Abstract: Achieving learning outcome requires a set of the material that can be understood easily by the students. The material should be appropriate in the learning process. It should give the opportunity for the students to learn both in the classroom and out of the classroom. The students can learn independently by using the appropriate material. However, the material of Basic English Grammar is still quite enough to give a chance for the students to practice and learn cooperatively. This research is aimed obtain e-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…As a lecturer, we are obligated to contribute to education to build effective teaching media for students (Ahmad, 2017). Therefore, Padlet based materials for Mechanical Engineering students have been designed in the previous research to enhance students' English ability.…”
Section: Introductionmentioning
confidence: 99%
“…As a lecturer, we are obligated to contribute to education to build effective teaching media for students (Ahmad, 2017). Therefore, Padlet based materials for Mechanical Engineering students have been designed in the previous research to enhance students' English ability.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the e-module should be carefully designed by taking into account learning principles and using consistent fonts, spacing, and layout. Ahmad (2017) stated that by developing an e-module based on the students need, educators can give the students appropriate material for their independent learning and may benefit in some aspects, such as providing flexibility for adapting and connecting developed materials to students' and institutional needs, enhancing the expertise of the writer, and raising the institution's reputation. The study from Pombo, Smith, Abelha, Caixinha, and Costa (2012) that evaluates the implementation of e-module revealed that implementing an e-module can help develop ICT skills, encourage self-reflection, and make task activities more engaging.…”
Section: E-modulementioning
confidence: 99%
“…An online module is characterized as a group of a few structural pieces that are joined to build a more complicated unit (Kusumawati et al, 2018). It is a term used to describe an educational learning platform that consists of a few units of online learning materials (Ahmad, 2017). It is a flexible learning technique that encourages university students to learn on their own time and terms.…”
Section: Employing Online Module In English-speaking Skills Learningmentioning
confidence: 99%